Long-term effects of whole body cryostimulation on uric acid concentration in plasma of secondary progressive multiple sclerosis patients. (December 2013) - Miller, Elżbieta; Saluk, Joanna; Morel, Agnieszka; Wachowicz, Barbara
Abstract Background. Uric acid (UA) has been suggested to be a marker of multiple sclerosis (MS) activity. Whole body cryostimulation (WBCT) is a new form of additional treatment and becoming popular in medicine. Objectives. The aims of this study were to determine the long-term effects of WBCT on the level of plasma UA in selected group of MS patients only with secondary progressive (SPMS) clinical form and verify results with functional state of patients assessed by expanded disability status scale (EDSS). Materials and methods. SPMS patients (n = 22) and healthy controls (n = 22) participated in 10 3-min-long exposures of WBCT (one exposure per day). Results were collected before the WBCT treatment and after completion the WBCT series as well as one and three months later. Results. WBCT increased UA concentration in plasma of SPMS patients not only directly after 10 exposures (p < 0.0001) but also one (p < 0.0001) and three (p < 0.005) months later. Furthermore, WBCT causes positive changes in EDSS scale both directly after WBCT (7% lower) and maintain this level 1month later as well as 3 month later (5% lower). Conclusions. WBCT may be used as adjuvant therapy via increase UA blood level; it improves functional status of SPMS patients.